An Econometric Analysis of the Determination of Prices in Manufacturing Industries - Straszheim, Donald H.; Straszheim, Mahlon R. (The Review of Economics and Statistics, 1976)
Donald H. Straszheim, Mahlon R. Straszheim, An Econometric Analysis of the Determination of Prices in Manufacturing Industries, The Review of Economics and Statistics, Vol. 58, No. 2 (May, 1976), pp. 191-201